2010
DOI: 10.1111/j.1365-313x.2010.04336.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of folate polyglutamylation and its essential role in plant metabolism and development

Abstract: SUMMARYCellular folates function as co-enzymes in one-carbon metabolism and are predominantly decorated with a polyglutamate tail that enhances co-enzyme affinity, subcellular compartmentation and stability. Polyglutamylation is catalysed by folylpolyglutamate synthetases (FPGSs) that are specified by three genes in Arabidopsis, FPGS1, 2 and 3, which reportedly encode plastidic, mitochondrial and cytosolic isoforms, respectively. A mutational approach was used to probe the functional importance of folate polyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 81 publications
6
94
0
Order By: Relevance
“…The lack of any obvious embryonic and shoot defects in atdfb supports recent reverse genetic studies suggesting that AtDFC or AtDFD is able to compensate for the absence of AtDFB during embryo and aboveground vegetative development (Mehrshahi et al, 2010). However, a novel finding from our studies is that these other FPGS isoforms do not always function redundantly, at least within a specific window of postembryonic root development.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…The lack of any obvious embryonic and shoot defects in atdfb supports recent reverse genetic studies suggesting that AtDFC or AtDFD is able to compensate for the absence of AtDFB during embryo and aboveground vegetative development (Mehrshahi et al, 2010). However, a novel finding from our studies is that these other FPGS isoforms do not always function redundantly, at least within a specific window of postembryonic root development.…”
Section: Discussionsupporting
confidence: 45%
“…In a recent reverse genetics study, various double mutant combinations of these Arabidopsis FPGS isoforms resulted in dramatic developmental phenotypes, providing compelling evidence for the importance of polyglutamylated folates in plant development (Mehrshahi et al, 2010). However, because single FPGS mutants did not appear to have any obvious defects in the aboveground organs of mature plants that were grown directly from soil, it was concluded that redundancy in compartmentalized FPGS activity is likely operating during plant development (Mehrshahi et al, 2010). In this study, we show that disruption of a gene encoding a single FPGS isoform (AtDFB) resulted in a dramatic reduction in primary root elongation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations